The impact of dimensionality reduction of ion counts distributions on preserving moments, with applications to data compression - da Silva, D.; Bard, C.; Dorelli, J.; Kirk, M.; Thompson, B.; Shuster, J. (Frontiers in Astronomy and Space Sciences, 2023)
The field of space physics has a long history of utilizing dimensionality reduction methods to distill data, including but not limited to spherical harmonics, the Fourier Transform, and the wavelet transform. Here, we present a technique for performing dimensionality reduction on ion counts distributions from the MMS/FPI instrument using a data-adaptive method powered by neural networks. This has applications to both feeding low-dimensional parameterizations of the counts distributions into other machine learning algorithms, and the problem of data compression to reduce transmission volume for space missions. The algorithm presented here is lossy, and in this work, we present the technique of validating the reconstruction performance with calculated plasma moments under the argument that preserving the moments also preserves fluid-level physics, and in turn a degree of scientific validity. The method presented here is an improvement over other lossy compressions in loss-tolerant scenarios like the MMS/FPI Fast Survey or in non-research space weather applications.